An improved RFID authentication protocol based on quadratic residue - Zhiliang LIU (Dianxin kexue)
In view of the existing radio frequency identification(RFID) authentication protocol based on quadratic residue in the security and cost aspects of the loopholes and deficiencies,an improved RFID bidirectional authentication protocol based on the quadratic residue was designed.The improved protocol was mixed with random number encryption under the framework of the quadratic residue,which makes the message certification and identification more efficient and fast in database authentication and identification; the ultra-lightweight bit replacement operations and XOR encryption communication information was introduced,which reduces the cost of system computing; in database,the random number checking mechanism was added to avoid attacks such as agreement to be synchronized and denial of service attacks; finally,the GNY logical proof of the protocol was given,which shows the feasibility of the improved protocol.The protocol security and performance analysis indicate that the improved protocol has higher security and lower cost.